2000
DOI: 10.1002/1529-0131(200010)43:10<2248::aid-anr12>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 1 and β2 integrins in C1q-stimulated superoxide production by human neutrophils: An example of a general regulatory mechanism governing acute inflammation

Abstract: Objective. To investigate the role of intercellular adhesion molecule 1 (ICAM-1) and ␤2 integrins in the production of superoxide (O 2 ؊ ) by C1q-stimulated human polymorphonuclear leukocytes (PMN).Methods. PMN were pretreated with F(ab) 2 fragments of monoclonal antibodies (mAb) that blocked or did not block ␤2 integrin-mediated adhesion. The cells were added to wells coated with C1q, and the production of O 2 ؊ was monitored kinetically as a color change due to reduction of cytochrome c. In some experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
(44 reference statements)
2
7
1
Order By: Relevance
“…Immobilized C1q induces PMN to make and release superoxide (47,48). The PMN receptor that mediates this response is not CR1 (48). Others have found that rabbit anticC1qR partially inhibits C1q-mediated superoxide production by PMN (21), a finding we have confirmed using anti-CRT IgY against a peptide of amino acid residues 24 -43 (data not shown).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Immobilized C1q induces PMN to make and release superoxide (47,48). The PMN receptor that mediates this response is not CR1 (48). Others have found that rabbit anticC1qR partially inhibits C1q-mediated superoxide production by PMN (21), a finding we have confirmed using anti-CRT IgY against a peptide of amino acid residues 24 -43 (data not shown).…”
Section: Discussionsupporting
confidence: 65%
“…In equilibrium binding assays, C1q collagen tail binding to purified CRT requires low ionic strength buffer, as does binding to CR1 (40,46); whereas C1q globular domains bind to adjacent sites in recombinant CRT in normal ionic strength buffer (8). Immobilized C1q induces PMN to make and release superoxide (47,48). The PMN receptor that mediates this response is not CR1 (48).…”
Section: Discussionmentioning
confidence: 99%
“…MBL binds to a wide array of carbohydrate structures on microbial surfaces and is believed to mediate direct killing via complement activation (4 -9) or by enhancing phagocytosis by acting as an opsonin (10,11). Recently, complement receptor 1 (CR1/CD35) has been defined as the cellular receptor for MBL (12,13), a finding consistent with the structural relatedness of MBL to C1q, which also binds to CR1 (14,15). MBL is associated with three novel MBL-associated serine proteases (MASPs), MASP-1 (16,17), MASP-2 (18), and MASP-3 (19).…”
Section: Annan-binding Lectin (Mbl)mentioning
confidence: 76%
“…In our experiments, we used stimulated neutrophils as the source of superoxide. Granulocytes (neutrophils or eosinophils) that arrive in the focus of allergic inflammation are activated through their cell surface receptors, including their integrins, which transmit signals and activate NADPH oxidase if appropriate inflammatory mediators, such as activated complements, are present in the tissue [42][43][44]. ROS produced by activated granulocytes in turn enhance eosinophil adhesion to VCAM-1 and thus recruit more eosinophils.…”
Section: Discussionmentioning
confidence: 99%